A New Lossless Fault-Tolerance Mechanism in Hybrid Wireless-Optical Broadband Access Network - Hong Zhang; Ruyan Wang; Honggang Wang; Guangkai Wu (IEEE Access, 2018)
With the tremendous growth of the traffic demand of emerging 5G applications, the survivability has become more significant in the wireless-optical broadband access network (WOBAN), since any failure of the network components could interrupt a large amount of traffic. A large amount of data could be lost even if there is a very short interruption. Previous works focus on finding the alternate paths or deploying backup fiber to recover the interrupted traffic. However, these works encounter three potential problems. First, the deployment of a backup fiber could increase the cost of recovery. Second, they must reroute the interrupted traffic to the backup resources, which could cause a long recovery time. Third, a large number of network packets could be lost during the recovery processes. To address these problems, a lossless fault-tolerance mechanism combining with parallel routing and network coding (LFTM-PR-NC) is proposed in this paper to enhance the survivability of WOBAN against any optical network unit-level and wireless-level failures. Numerical results show that the proposed LFTM-PR-NC mechanism significantly outperforms the previous mechanism. Meanwhile, the LFTM-PR-NC mechanism could dramatically decrease the recovery time when a failure occurs.